2017
DOI: 10.1097/mat.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Simulation Comparing a Cavopulmonary Assist Device and VA ECMO for Failing Fontan Support

Abstract: A cavopulmonary assist device (CPAD) has been developed for failing Fontan support. This CPAD pumps blood from superior/inferior vena cavae (SVC/IVC) to pulmonary artery. In this study, we compared failing Fontan support with CPAD versus veno-arterial extracorporeal membrane oxygenation (VA ECMO) in silico. A numerical lumped-parameter circulatory system model was used to simulate Fontan circulation. Failing Fontan was simulated by increased pulmonary resistance. Central venous pressure (CVP), mean pulmonary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Through simulations, we showed that a proper implementation of an arterial pump in the right circulation could benefit the Fontan hemodynamics. We constructed the failing Fontan model employing clinical data available in the literature and found that the failing circulation model to be in general agreement with previous reports [16], [18], [35]. Our model sensitivity analysis showed the association of the hemodynamic parameters (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…Through simulations, we showed that a proper implementation of an arterial pump in the right circulation could benefit the Fontan hemodynamics. We constructed the failing Fontan model employing clinical data available in the literature and found that the failing circulation model to be in general agreement with previous reports [16], [18], [35]. Our model sensitivity analysis showed the association of the hemodynamic parameters (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…The lower limb circulation is further divided into the iliac artery and arterial and venous networks of the leg, using the same technique as published in our 13-compartments Fontan circulation. 3…”
Section: Methodsmentioning
confidence: 99%
“…The simulation based on LPM greatly reduced computational expense compared to 3-dimensional computational fluid dynamics 1 and can produce hemodynamics in agreement with clinical data. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling and comparison of VV ECMO with DLC to other cardiopulmonary assist device designs further aided development. 13 Recently, a DLC-based ambulatory cardiopulmonary assist (CPA) system for a failing Fontan sheep model was developed by Wang and colleagues. 14 The percutaneous DLC CPA is designed for insertion and advancement into the right internal jugular vein, to the SVC, through the Fontan connection, and finally into the IVC.…”
Section: Modified Veno-venous Ecmo Techniquesmentioning
confidence: 99%
“…While this allows more consistent cardiopulmonary perfusion, the risk of thrombosis in stagnant areas persists and must be considered. Mathematical modeling and comparison of VV ECMO with DLC to other cardiopulmonary assist device designs further aided development 13 …”
Section: Modified Veno‐venous Ecmo Techniquesmentioning
confidence: 99%